Actions taken as part of the health policy of the Republic of Poland during the Covid-19 pandemic - Kacprowska, Krystyna (Polityka i Społeczeństwo, 2022)
The coronavirus pandemic has become a stimulus to introduce changes in the functioning of societies and to take health policy measures aimed at effective fight against the pandemic. Counteracting the spread of the virus and mitigating its negative effects are a challenge even for countries with organized health services. Several restrictions were introduced in health policy during the COVID-19 pandemic, but the pandemic remains a challenge that requires further action. The aim of this study was to analyze the activities undertaken in Poland as part of health policy. To find an answer to the presented research question, a literature review was carried out, which provided information on the functioning of health policies, programs and intervention techniques that were introduced in the fight against the pandemic.